An intrinsic association between olfactory identification and spatial memory in humans - Louisa Dahmani (Nature Portfolio, 2018)
Olfaction, the sense of smell, may have originally evolved to aid navigation in space, but there is no direct evidence of a link between olfaction and navigation in humans. Here the authors show that olfaction and spatial memory abilities are correlated and rely on similar brain regions in humans.